The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.4315/0362-028x-60.9.1041
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Listeria monocytogenes in Frozen Ewe's Milk and Feta Cheese Curd

Abstract: Pasteurized whole ewe's milk was inoculated to contain ca. 1.0 × 106 to 2.0 × 106 Listeria monocytogenes Scott A or California (CA). Inoculated milk samples of 200 ml in sterile stomacher bags were frozen at −38°C and stored at −18 or −38°C for 7.5 months. Inoculated milk was also made into Feta cheese curd, according to a standard procedure. After 5 h of drainage, curd samples of 200 g in sterile stomacher bags were frozen at −38°C, and stored at −18 or −38°C for 7.5 months. The pH values of the ewe's milk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…In sheep milk, frozen at -38 0 C, and subsequently stored at -18 0 C and -38 0 C during the period of 7,5 months, one strain of L.monocytogenes survived to great extent ( 95% ), whereas the other strain, under same conditions, survived in a lesser degree (40-50%). Destroying of L. monocytogenes in curdle of feta cheese obtained from said sheep milk stored under same conditions, was greater than in sheep milk (Papageorgiou et al, 1997). To which extent the L. monocytogenes develops or survives in milk and dairy products, stored at storage temperature or frozen, depends on the type of dairy product and strain of L. monocytogenes (El-Gazar et al, 1992;Theodoridis et al, 2006).…”
Section: Presence Of L Monocytogenes In Milk and Dairy Productsmentioning
confidence: 99%
“…In sheep milk, frozen at -38 0 C, and subsequently stored at -18 0 C and -38 0 C during the period of 7,5 months, one strain of L.monocytogenes survived to great extent ( 95% ), whereas the other strain, under same conditions, survived in a lesser degree (40-50%). Destroying of L. monocytogenes in curdle of feta cheese obtained from said sheep milk stored under same conditions, was greater than in sheep milk (Papageorgiou et al, 1997). To which extent the L. monocytogenes develops or survives in milk and dairy products, stored at storage temperature or frozen, depends on the type of dairy product and strain of L. monocytogenes (El-Gazar et al, 1992;Theodoridis et al, 2006).…”
Section: Presence Of L Monocytogenes In Milk and Dairy Productsmentioning
confidence: 99%
“…Marth (1990, 1991) observed an initial decrease of L. monocytogenes population in frozen milk and in frozen milk components over 7 weeks. Papageorgiou et al (1997) also showed that L. monocytogenes survived for 7.5 months in frozen ewe's milk and feta cheese curd, and the data indicate a decrease of 98% in L. monocytogenes population during frozen storage of curd at −38°C or −18°C for up to 7.5 months. Furthermore, their data indicated that strain Scott A can survive frozen storage at a higher percentage (60-80%) than strain California.…”
Section: Discussionmentioning
confidence: 82%
“…Επιπλζον ζχει αναωερκεί, ότι θ διάρκεια τθσ λανκάνουςασ ωάςθσ για κφτταρα τθσ L. monocytogenes, που ζχουν προθγουμζνωσ καλλιεργθκεί ςε χαμθλζσ κερμοκραςίεσ, είναι μειωμζνθ ςε ςχζςθ με τα αντίςτοιχα που ζχουν αυξθκεί ςε κερμοκραςίεσ περιβάλλοντοσ (Whiting και Bagi, 2002). Κατά τθν ςυντιρθςθ των τροωίμων ςε κερμοκραςίεσ κατάψυξθσ δφναται να παρατθρθκεί επιβίωςθ του πλθκυςμοφ των κυττάρων του πακογόνου ι μείωςι του, ανάλογα με ςτζλεχοσ και το υπόςτρωμα (Papageorgiou et al, 1997, Gougouli et al, 2008. Θ ανκεκτικότθτα του μικροοργανιςμοφ ςτισ χαμθλζσ κερμοκραςίεσ επιτυγχάνεται μζςω τθσ ενδοκυτταρικισ ςυςςϊρευςθσ των ςυμβατϊν διαλυτϊν ενϊςεων γλυκίνθβεταΐνθ και καρνιτίνθ (Angelidis et al, 2002).…”
Section: ανκεκτικότθτα του μικροοργανιςμοφ ςε περιβαλλοντικοφσ παράγοντεσ 1251 επίδραςθ τθσ κερμοκραςίασunclassified